Untargeted Lipidomics Reveals a Specific Enrichment in Plasmalogens in Epicardial Adipose Tissue and a Specific Signature in Coronary Artery Disease - Barchuk, Magalí (2020)
OBJECTIVE:Epicardial adipose tissue (EAT) is an active endocrine organ that could contribute to the pathophysiology of coronary artery disease (CAD) through the paracrine release of proatherogenic mediators. Numerous works have analyzed the inflammatory signature of EAT, but scarce informations on its lipidome are available. Our objective was first to study the differences between EAT and subcutaneous adipose tissue (SAT) lipidomes and second to identify the specific untargeted lipidomic signatures of EAT and SAT in CAD. Approach and Results: Subcutaneous and EAT untargeted lipidomic analysis was performed in 25 patients with CAD and 14 patients without CAD and compared with paired plasma lipidomic analysis of isolated VLDL (very low-density lipoprotein) and HDL (high-density lipoprotein). Lipidomics was performed on a C18 column hyphenated to a Q-Exactive plus mass spectrometer, using both positive and negative ionization mode. EAT and SAT had independent lipidomic profile, with 95 lipid species differentially expressed and phosphatidylethanolamine 18:1p/22:6 twenty-fold more expressed in EAT compared with SAT false discovery rate =3×10-4). Patients with CAD exhibited more ceramides (P=0.01), diglycerides (P=0.004; saturated and nonsaturated), monoglycerides (P=0.013) in their EAT than patients without CAD. Conversely, they had lesser unsaturated TG (triglycerides; P=0.02). No difference was observed in the 295 lipid species found in SAT between patients with and without CAD. Fifty-one lipid species were found in common between EAT and plasma lipoproteins. TG 18:0/18:0/18:1 was found positively correlated (r=0.45, P=0.019) in EAT and HDL and in EAT and VLDL (r=0.46, P=0.02).CONCLUSIONS:CAD is associated with specific lipidomic signature of EAT, unlike SAT. Plasma lipoprotein lipidome only partially reflected EAT lipidome.